MEDVEDEV-SARKOZY’S SIX POINTS: THE DIPLOMATIC ASPECT OF THE SOUTH OSSETIAN SETTLEMENT - VOLKHONSKIY, Mikhail (CENTRAL ASIA AND THE CAUCASUS, 2009)
The August 2008 events in South Ossetia marked an important stage in the recent history of the Southern Caucasus: they changed the course of the region’s sociopolitical life and have become the axis of the very complicated relations among the biggest international players. The conflict settlement was achieved through a fairly long diplomatic struggle, which faithfully reflected the relations among Russia, the United States, and the European Union. Below I offer an analysis of the diplomatic aspect of the South Ossetian settlement. The tension between Tskhinvali and Tbilisi, which cropped up early in 2008, had developed, by August, into a series of armed provocations and clashes. In a diplomatic effort to defuse the situation Russia relied, very much as before, on the Joint Control Commission for the settlement of the Georgian-Ossetian conflict (JCC); Tbilisi, which refused to back off from its South Ossetian position, made these efforts futile. Back in March 2008, Georgia, dissatisfied with the balance of votes in the JCC (one Georgian against three from the South Ossetian “lobbyists”) left the structure. This was obviously done to elbow Moscow out of the regional decision-making. This plan required a much worsened situation; Russia’s image as an intermediary should have been discredited. Between March and August 2008, Georgia consistently destabilized the situation in South Ossetia. Late on 7 August, 2008, America’s interference somewhat stabilized the situation; the Georgian side announced a unilateral ceasefire.1 Russian diplomats convinced the sides to meet for talks on 8 August outside the JCC on the condition that the Commission would remain the only negotiation format.